THE MORTALITY AND MORBIDITY ASSOCIATED WITH UMBILICAL CORD PROLAPSE - Waqar, Fareesa; Nisa, Aziz -un-; Begum, Nazakat (Journal of Ayub Medical College Abbottabad, 1996)
A prospective study was carried out on 15 cases of cord prolapse admitted in the study period between January 1995 and December 1995 in Gynae "A" unit at Women and Children Teaching Hospital, Abbottabad. managing 15(H) deliveries annually. Survival rates were assessed by APGAR score at 1 and 5 minutes. The incidence of cord prolapse was 1 in 100 in our study group. H babies were alive when cord prolapse was diagnosed and all except 1 survived inspite of severe bradycardia. Reason for low mortality rate of hospital diagnosed cases with alive fetuses was a short diagnosis to delivery interval (D.D.I.).